LOCAL OWN REVENUE, DECENTRALIZATION AND LOCAL FINANCIAL INDEPENDENT - Purnama Sari; Isep Saepul Muzaki; Nurdiana Mulyatini; Eva Faridah; Benny Prawiranegara (Jurnal Manajemen Indonesia, 2019)
The regional autonomy system provides an opportunity for regions in the territory of Indonesia to utilize their sources of income independently so that the implementation of development in the regions does not only rely on finance from the central government. In this study, we are of the opinion that regions that are able to optimize their local own revenue will have an impact on increasing local financial independence. Local financial independence is the ability of a region to finance development in its area. Our other opinion assumes that the relationship between localown revenue and the local financial independence can be strengthened by the implementation of decentralization. With good decentralization, local governments are more transparent in providing all information to the public, can increase accountability because public services are getting closer, local governments can take strategic decisions, improve fiscal management, improve economic growth and market security. The new contribution of this study is related to the literature of the merging of the relationship between local own revenue, decentralization, and local financial independence that was built through Moderated Regression Analysis (MRA) evidence in one of the regions in Indonesia, namely Ciamis. The results of the study show that regional local own revenues influence local financial independence. Meanwhile, decentralization which is proxied using local government expenditures is able to strengthen the relationship of local own revenues to local financial independence. So it can be concluded that the effective implementation of decentralization is able to encourage an increase in regional income that comes from its own sources to realize financial independence in the region. Keywords—Decentralization, Local Financial Independent, Local Own Revenue. Abstrak Sistem otonomi daerah memberikan kesempatan kepada daerah-daerah di wilayah Indonesia untuk memanfaatkan sumber-sumber pendapatannya secara mandiri agar pelaksanaan pembangunan di daerah tidak hanya mengandalkan keuangan yang berasal dari pemerintah pusat. Dalam studi ini, kami berpendapat bahwa daerah yang mampu mengoptimalkan pendapatan asli daerahnya akan berdampak terhadap meningkatnya kemandirian keuangan daerah. Kemandirian keuangan daerah adalah kemampuan suatu daerah dalam membiayai pembangunan di daerahnya. Pendapat kami lainnya menganggap bahwa hubungan pendapatan asli daerah dengan kemandirian keuangan daerah dapat diperkuat oleh pelaksanaan desentralisasi yang baik. Dengan desentralisasi yang baik maka pemerintah daerah lebih transparan dalam memberikan semua informasi kepada publik, dapat meningkatkan akuntabilitas karena pelayanan publik menjadi lebih dekat, pemerintah daerah dapat mengambil keputusan yang strategis, meningkatkan manajemen fiscal, meningkatkan pertumbuhan ekonomi dan keamanan pasar. Kontribusi baru dari studi ini adalah menyangkut literature penggabungan hubungan antara pendapatan asli daerah, desentralisasi, dan kemandirian keuangan daerah yang dibangun melalui Moderated Regression Analysis (MRA) bukti pada salah satu daerah di Indonesia, yaitu Ciamis. Hasil studi menunjukan bahwa pendapatan asli daerah berpengaruh terhadap kemandirian keuangan daerah. Sementara itu desentralisasi yang diproksi menggunakan pengeluaran pemerintah daerah mampu memperkuat hubungan pendapatanasli daerah terhadap kemandirian keuangan daerah. Jadi dapat disimpulkan bahwa pelaksaksanaan desentralisasi yang efektif mampu mendorong peningkatan pendapatan daerah yang berasal dari sumber-sumbernya sendiri untuk mewujudkan kemandirian keuangan di daerah. Kata kunci—Desentralisasi, Kemandirian Keuangan Daerah, Pendapatan Asli Daerah.